Application of the Proportion of Sediment-sensitive Invertebrates (PSI) biomonitoring index - Extence, Chris A.; Chadd, Richard P.; England, Judy; Naura, Marc; Pickwell, A. G. (Wiley, 2017)
Sedimentation of river beds is a key pressure impacting riverine ecological communities. Research has identified the need for new approaches to help demonstrate and quantify the impacts of excessive fine-sediment deposition on benthic macroinvertebrate populations. To help meet this requirement, the Proportion of Sediment-sensitive Invertebrates (PSI) methodology was developed and has been in operational use in the United Kingdom for several years. This paper presents a number of case studies, at both national and local scales, showing how the method can be used to identify point and nonpoint fine-sediment pollution, as well as demonstrating the analysis of a national dataset to describe the relationship between PSI and a channel substrate index. A novel approach to displaying PSI data alongside local ecological and hydrological information is also presented and interpreted, to illustrate how improved understanding of biotic and abiotic relationships and interactions can be readily accomplished. Excessive fine-sediment accumulation on river beds results in impaired ecosystem health globally. The case studies and examples presented here will provide confidence that the PSI method can form the basis for evidence gathering and analysis, both within and beyond the United Kingdom. The paper concludes with an overview of the use of PSI in catchment research and management, a consideration of the relationship of the metric with other macroinvertebrate indices, and a summary of refinements recently applied to the index.
Keywords: Aquatic macroinvertebrates; Catchment management; Fine sediment; Multimetric analysis; PSI index